Monitoring various eluate characteristics of the iThemba LABS SnO2-based 68Ge/68Ga generator over time and validation of quality control methods for the radiochemical purity assessment of 68Ga-labelled DOTA peptide formulations - Davids, Claudia Ruby (Stellenbosch : Stellenbosch University, 2017)
Thesis (MSc)--Stellenbosch University, 2017.